Appalili and Katto Bokko Agrarian Rites of the Indigenous People of Kekaraengan Marusu in Maros Regency - Muhammad Azhar Husnan; Alya Daniyah Rosyadah; Andi Usrawi Mappaseng (UNIVERSITAS PAKUAN, 2026)
This research will examine the existence, changes, and social impacts of two agrarian rites belonging to the Kekaraengan Marusu Indigenous People in the Kassi Kebo Environment, Bajubodoa Village, Maros Baru District, Maros Regency. Namely the Appalili rite, as a marker of the rice planting season and the Katto Bokko rite as a marker of the harvest season. Motivated by the threat of the sustainability of these two rites in line with the shift in the economic structure of Maros Regency from the agricultural sector to the increasingly massive transportation, warehousing, and processing industry sectors, as stated in the